Wood apple (Kaith):A nutritious underutilized fruit - Tripathi, Prakash Chandra (Indian Horticulture, 2025)
Wood apple (Feronia limonia syn. Limonia acidissima), an underutilized arid zone fruit of the Rutaceae family, is valued for its nutritional richness, medicinal properties, and diverse uses. Native to India, it thrives in tropical and subtropical climates, tolerating drought and poor soils. The pulp is high in pectin, carbohydrates, proteins, vitamins (A, B-complex, C), minerals, and fiber, supporting gastrointestinal health and various culinary applications. It remains underutilized despite its potential for income generation, climate-resilient farming, systematic cultivation, varietal enhancement, and improved post-harvest management. Promoting wood apple through crop diversification programs can enhance rural livelihoods, food security, and sustainability under changing climate conditions.